HOTS-Based Learning in Junior High Schools and Its Implication on Teachers’ Professional Development - Nofrina Eka Putri; Fairoza Fairoza; Nadra Mardalena; Cici Afriyeni; Sania Lanen (AL-ISHLAH: Jurnal Pendidikan, 2022)
AbstractRecently, there have been lots of trainings aimed at equipping teachers with knowledge and skills in designing HOTS-based learning and assessment, but do teachers transfer what they have acquired to the classroom appropriately? This descriptive qualitative research then seeks to reveal how HOTS-based learning conducted by teachers who have joined trainings on HOTS-based learning and assessment, and its implication toward their professional development in Junior High Schools. The subjects of the research were 3 teachers teaching English in 3 different Junior High Schools in West Sumatera. The data were obtained through interview. The results of the research indicate that the teachers have already had clear understanding on the nature of HOTS, but HOTS-based learning is not yet optimally conducted at school due to the teachers’ less capability in translating the knowledge on HOTS into practical activities. Furthermore, it is found that HOTS-based trainings and workshops offered so far seem more intended to equip teachers to design HOTS-based questions for testing purposes. Hence, the results imply that the upcoming trainings or workshop provided for the teachers should balance the needs for assessment and the needs for learning materials and activities. They should also be strengthened with coaching programs to help the teachers correctly apply what they have acquired, especially in designing materials and learning activities.  AbstrakBelakangan ini banyak pelatihan yang ditujukan untuk membekali guru dengan pengetahuan dan keterampilan dalam merancang pembelajaran dan penilaian berbasis HOTS, tetapi apakah guru sudah mengaplikasikan apa yang telah mereka peroleh di kelas dengan tepat? Penelitian deskriptif kualitatif ini bertujuan untuk mengungkap bagaimana pembelajaran berbasis HOTS dilakukan oleh guru yang telah mengikuti pelatihan pembelajaran dan asesmen berbasis HOTS, serta implikasinya terhadap pengembangan profesional mereka di SMP. Subjek penelitian ini adalah 3 guru yang mengajar bahasa Inggris di 3 SMP yang berbeda di Sumatera Barat. Data diperoleh melalui wawancara. Hasil penelitian menunjukkan bahwa guru sudah memiliki pemahaman yang baik mengenai hakikat HOTS, namun pembelajaran berbasis HOTS belum optimal dilakukan di sekolah karena guru kurang mampu menerjemahkan pengetahuan tentang HOTS ke dalam kegiatan praktik. Lebih lanjut, ditemukan bahwa pelatihan dan lokakarya berbasis HOTS yang ditawarkan selama ini tampaknya lebih ditujukan untuk membekali para guru dalam merancang soal-soal ujian berbasis HOTS. Hasil ini menyiratkan bahwa pelatihan atau lokakarya yang akan datang yang disediakan untuk para guru harus menyeimbangkan kebutuhan asesmen dengan kebutuhan materi dan kegiatan pembelajaran. Mereka juga harus diperkuat dengan program pendampingan untuk membantu para guru menerapkan dengan benar apa yang telah mereka peroleh, terutama dalam merancang materi dan kegiatan pembelajaran.